STUDENT WORKSHEETS DEVELOPMENT BASED SCIENCE PROCESS SKILLS ON MATERIAL FACTORS AFFECTING CHEMICAL EQUILIBRIUM - septiana dewi susanti; Noor Fadiawati; chansyanah diawati (Universitas Lampung, 2012)
This research aims to produce student worksheets based science process skills on material factors affecting chemical equilibrium. The research methodused is theResearchand Development. Subject of this research is student worksheets based science process skills. Limited testing judgments of teachers and students' response to student worksheets developed by the student worksheetsbased science process skills on material factors affectingchemical equilibrium. The resultsofteacherassessmentsof thesuitabilitythe content andreadabilityis goodwith percentage 84.28% and 84% andthe results ofthe students'responseto thereadabilityand beauty, that students' responsetoreadabilityis as high as withpercentage82.5%andfor the beauty ofthe students' responseis as high as with percentage 85%. Keywords :student worksheets, science process skills, and factors affecting chemical equilibrium